Savoy [compact disc] - Taj Mahal (Musician); Caron, Danny; Davies, Ruth (Double bassist); Simon, John, 1941-; Joyce, Leon (Stony Plain, 2023)
Taj Mahal can rightfully be called a living legend for his contributions to popular music. With a voice as instantly recognizable as Louis Armstrong, Ray Charles, or Dr John, Taj Mahal has throughout his career pushed the envelope of American music forward by incorporating sounds from the Caribbean, Africa, traditional blues, and jazz. With this release, Taj takes a new direction in his musical journey, exploring classics from the American songbook with his good friend and acclaimed record producer John Simon, whose resume includes producing classic albums by The Band, Janis Joplin, Leonard Cohen, Blood, Sweat & Tears, Simon & Garfunkel, and Michael Franks. This is the realization of a musical collaboration they had been planning for decades.